Transcatheter Aortic Valve Replacement for Aortic Regurgitation – A Review - Ran Liu; Zhaolin Fu; Jing Yao; Yunfeng Yan; Guangyuan Song (Cardiovascular Innovations and Applications, 2023)
Transcatheter aortic valve replacement (TAVR) is currently a widely used option for patients with severe symptomatic aortic stenosis with high to low surgical risk. However, aortic regurgitation (AR) remains an “off-label” indication for TAVR, particularly for patients with mild or absent leaflet calcification or aortic annulus dimensions beyond the size of the bioprosthesis, which increase the risk of dislocation. With advances in transcatheter heart valve devices, the safety and efficacy of TAVR in treating patients with severe pure native AR has gained acceptance. This review examines current evidence and clinical practice, and presents technological advancements in devices for AR.